2020
DOI: 10.3389/fmicb.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulated Periplasmic Glucans Transmit External Signals Through Rcs Phosphorelay Pathway in Yersinia enterocolitica

Abstract: Fast response to environmental changes plays a key role in the transmission and pathogenesis of Yersinia enterocolitica. Osmoregulated periplasmic glucans (OPGs) are known to be involved in environmental perception of several Enterobacteriaceae pathogens; however, the biological function of OPGs in Y. enterocolitica is still unclear. In this study, we investigated the role of OPGs in Y. enterocolitica by deleting the opgGH operon encoding enzymes responsible for OPGs biosynthesis. Complete loss of OPGs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The intracellular c-di-GMP concentration was measured as previously described (Meng et al, 2020). Briefly, the third-round of cultivated bacterial cells was 50-fold diluted, respectively, into 2 ml of fresh LB broth, LB supplemented with 100 µM DP, and LB supplemented with 40 µM FeSO 4 in a 5-ml glass tube and allowed to grow at 30 • C with shaking at 200 rpm to an OD 600 = 0.6∼0.8.…”
Section: Extraction and Quantification Of C-di-gmpmentioning
confidence: 99%
“…The intracellular c-di-GMP concentration was measured as previously described (Meng et al, 2020). Briefly, the third-round of cultivated bacterial cells was 50-fold diluted, respectively, into 2 ml of fresh LB broth, LB supplemented with 100 µM DP, and LB supplemented with 40 µM FeSO 4 in a 5-ml glass tube and allowed to grow at 30 • C with shaking at 200 rpm to an OD 600 = 0.6∼0.8.…”
Section: Extraction and Quantification Of C-di-gmpmentioning
confidence: 99%
“…Our previous data demonstrated that the Rcs phosphorelay represses flhDC, hmsHFRS, and hmsT in Y. enterocolitica [10,34]. The flhDC operon encodes the master regulator of flagella biosynthesis [10].…”
Section: Lps Truncation Caused By Waaf Deletion Activated the Rcs Phomentioning
confidence: 99%
“…Our previous data demonstrated that the Rcs phosphorelay represses flhDC, hmsHFRS, and hmsT in Y. enterocolitica [10,34]. The flhDC operon encodes the master regulator of flagella biosynthesis [10]. hmsHFRS and hmsT are genes involved in biofilm formation, of which hmsHFRS required for the biosynthesis of poly-β-1,6-N-acetylglucosamine exopolysaccharide and hmsT encoding diguanylate cyclase is essential for cyclic dimeric guanosine monophosphate (c-di-GMP) biosynthesis [35].…”
Section: Lps Truncation Caused By Waaf Deletion Activated the Rcs Phomentioning
confidence: 99%
See 2 more Smart Citations